ANALYSIS OF CHROMIUM (Cr) AND NICKEL (Ni) IN THE WEST COAST OF KARIMUN ISLAND RIAU ARCHIPELAGOS PROVINCE - Brilliant Esye Lousiana; Bintal Amin; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in March 2015 by collecting samples of water and sediments from the west coast of Karimun island. The purpose of this study was to determine the concentration of heavy metals chromium (Cr) and nickel (Ni) in seawater and sediments. Sample collection was done by purposive sampling method in which the three selected station. The highest Cr concentration in sea water was found in Station 2 (0.148 mg/L) and Ni in Station 3 (0.071 mg/L) whilst highest Cr and Ni concentrations in Station 2 (4.643 and 2.289 μg/g). Compared tothe Standard Quality Guideline for Sediment, the concentrations of Cr and Ni were still below the value of ERL and still very far below the value of ERM. In contrast with Ni, which has negative correlation with its concentration in sediment, the Cr concentration in sea water was positively correlated with its concentration in sediment.Keywords: Heavy Metals, Sediment, Seawater and Karimun